Competent workforce and vocational psychology - Abdul Rahman, Shukran (2018)
This paper highlights the objectives of higher education and Psychology Education. It deliberates the key learning area during students ‘ enrolment in higher learning institution; and specify the quality of graduates and their employability. The paper attempts to redefine eemployability vis a vis the domains adopted in the Holland’s Self Directed Search